HUBUNGAN MEKANISME KOPING DENGAN DISMENORE PADA MAHASISWA JURUSAN KEPERAWATAN FKIK UNIVERSITAS JENDERAL SOEDIRMAN PURWOKERTO - Desiyani Nani; Cahyo Ismawati; Keksi Girindra (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2010)
ABSTRACT Dysmenorrhoea is a kind of menstruation disturbance that happens to those who around 15-25 years old which is formed pain when menstruation. Dysmenorrhoea which happen in women to another women is different. People use coping mechanism to adaptation with their problem. This research was aimed to know the relationship between coping mechanism and dysmenorrhoea toward students at nursing program of FKIK Unsoed Purwokerto. This is a assosiative research with a cross-sectional approach. The population is all students at nursing program. The number of sample is 55 gained through simple random sampling. The research is conducted at nursing program, on October 2008. Research tool scale is a Visual Analog Scale. Data analysis using kendal tau. The result of the research show that sample which use maladaptive coping mecanism found 52,7% and sample which use adaptive coping mecanism found 47,3%. Students which use maladaptive coping mecanism divided into four groups namely: one student don’t get dysmenorrhoea, 13 students get low dysmenorrhoea, 11 students get medium dysmenorrhoe, 4 students get high dysmenorrhoea. Students which use adaptive coping mecanism divided into four groups namely, 3 students don’t get dysmenorrhoea, 9 students get low dysmenorrhoea, 12 students get medium dysmenorrhoea, 2 students get high dysmenorrhoea. Satistically, it was found that P=0,713 is more than significant value used (0,05). So, there is not significant relationship between coping mechanism and dysmenorrhoea toward students at nursing program. Key words: coping mechanism, dysmenorrhoea. Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 34-46